GENDER INEQUALITY IN ACCOUNTING PROFESSION FROM THE PERSPECTIVE OF THE GLASS CEILING - Silva, Júlio César; Dal Magro, Cristian Baú; da Silva, Marcia Zanievicz (RACE - Revista de Administração, Contabilidade e Economia, 2016)
Among the studies developed on gender differences in occupations, the theoretical glass ceiling approach has been used internationally to explain the occurrence of barriers that hinder and even prevent the professional growth of women and generate wage inequalities between men and women in the performance of similar functions. Given the above, the study aims to identify gender differences in the accounting profession analyzed from the perspective of the glass ceiling. The research methodology is descriptive, documentary and the approach is quantitative. Data were extracted from the Annual Social Information (RAIS), base year 2013. The investigated population are employees who work in accounting in companies located in southern Brazil. The results indicate that the professions of accounting auditor and accountant are performed, most often by male professionals. It was found that men have higher pay and a predominance of men in the accounting department of larger companies. We conclude that glass ceiling is present in the accounting profession, creating an invisible barrier to women's access to positions of greater evidence of the accounting profession. Keywords: Glass Ceiling. Gender. Accounting Professional. Inequality.